2002
DOI: 10.1016/s1525-1578(10)60698-8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of EWS-CHOP Fusion Gene in Two Cases of Myxoid Liposarcoma

Abstract: Fusion genes consisting of TLS/FUS and CHOP or EWS and CHOP are characteristic markers for myxoid/ round cell liposarcomas (MLS/RCLS). Several different structures of the fusion genes were reported in the case of the TLS/FUS-CHOP form, whereas only one type of structure has so far been found for the EWS-CHOP form, which consisted of exons 1 to 7 of the EWS and exons 2 to 4 of the CHOP gene. Here we describe a novel type of EWS-CHOP fusion gene in two cases of MLS/RCLS, which were found in a consecutive analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…[6][7][8] The finding that EWSR1 (22q12) can be substituted in the place of FUS (16p11) is not surprising as EWSR1 and FUS are both members of the TET family of RNA-binding proteins; indeed, EWSR1 has been found to replace FUS as the partner of CHOP (DDIT3)(12q13) in the gene fusions of myxoid/round cell liposarcomas. 17,18 Terra et al, found by screening with FISH probes for ATF1, that 4 of 14 cases (29%) harbored rearrangements of this gene. Of these four cases, three had the EWSR1/ATF1 fusion, whereas the remaining case displayed the FUS/ATF1 fusion.…”
Section: Fish Angiomatoid Fibrous Histiocytomamentioning
confidence: 99%
“…[6][7][8] The finding that EWSR1 (22q12) can be substituted in the place of FUS (16p11) is not surprising as EWSR1 and FUS are both members of the TET family of RNA-binding proteins; indeed, EWSR1 has been found to replace FUS as the partner of CHOP (DDIT3)(12q13) in the gene fusions of myxoid/round cell liposarcomas. 17,18 Terra et al, found by screening with FISH probes for ATF1, that 4 of 14 cases (29%) harbored rearrangements of this gene. Of these four cases, three had the EWSR1/ATF1 fusion, whereas the remaining case displayed the FUS/ATF1 fusion.…”
Section: Fish Angiomatoid Fibrous Histiocytomamentioning
confidence: 99%
“…At the molecular level, different breakpoints and exon combinations have been reported with different incidences (exon5-FUS/ exon3-CHOP frequency in MRLS 6%, exon8-FUS/exon2-CHOP frequency in MRLS 10%, exon7-FUS/exon2-CHOP frequency in MRLS 20%, up to 60% for exon5-FUS/ exon2-CHOP). [11][12][13][14][15][16][17] Therefore, detailed molecular analysis of breakpoints is highly suitable as a clonal marker. However, wide use is limited by the high frequency of the most common exon combinations (eg, exon5-FUS/ exon2-CHOP), resulting in an a priori chance of finding a distranslocation in two MLS cases irrespective of their clonal relation.…”
mentioning
confidence: 99%
“…As MLPS with cartilaginous differentiation is a rare condition, the differential diagnosis from other benign or malignant soft tissue sarcomas, such as chondroid lipoma, extraskeletal chondroma, extraskeletal myxoid chondrosarcoma and malignant mesenchymoma, is difficult. Although chondroid lipoma and extraskeletal chondroma have cells with a similar appearance to lipoblasts (6), the presence of a plexiform capillary vascular network, is a characteristic of MLPS. Myxoid chondrosarcomas are different in that they show chondrocyte atypia (19).…”
Section: Discussionmentioning
confidence: 99%
“…This translocation leads to fusion of fused in liposarcoma (FUS; also termed translocated in liposarcoma) and DNA damage-inducible transcript 3 (DDIT3; also termed CCAAT/enhancer-binding protein homologous protein) genes, resulting in the production of the FUS-DDIT3 fusion protein (5). In another subset of MLPS, a minor chromosomal translocation, t(12;22)(q13;q12), results in fusion of the Ewing's sarcoma (EWSR1) and DDIT3 genes (6). PLPS is less frequent and harbors a complex genomic profile with numerous gains and losses similar to the genomic profile observed in poorly differentiated sarcoma (7).…”
Section: Introductionmentioning
confidence: 99%